2021
DOI: 10.1002/osp4.584
|View full text |Cite
|
Sign up to set email alerts
|

Differences in mortality rate among patients hospitalized with severe COVID‐19 according to their body mass index

Abstract: Background Obesity has been described as a risk factor for COVID‐19 severity and mortality. Previous studies report a linear association between BMI and adverse outcomes, meanwhile in other critical illness, excessive fat tissue is related to improved survival. Whether different BMI is related with the survival of patients with severe COVID‐19 deserves further analysis. Objective To determine the mortality rate among hospitalized patients with severe COVID‐19 stratified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…17 A more recent study showed that patients with underweight, overweight, and grade 3 obesity were at higher risk of COVID-19 related mortality compared to patients with grade I or grade II obesity. 18 On the other hand a French study of 1461 critically ill patients with COVID-19 showed mortality was higher in patients with obesity class III (BMI ≥ 40 kg/m 2 ). 19 In this study, we examined the association between the BMI classes (patients with underweight [BMI < 18.5 kg/m 2 ], patients with normal weight [BMI 18.5-24.9 kg/m 2 ], patients with overweight [BMI 25-29.9 kg/m 2 ], and patients with obesity [BMI ≥ 30 kg/m 2 ]) and outcomes among patients hospitalized with COVID-19 in our innercity patient population.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 A more recent study showed that patients with underweight, overweight, and grade 3 obesity were at higher risk of COVID-19 related mortality compared to patients with grade I or grade II obesity. 18 On the other hand a French study of 1461 critically ill patients with COVID-19 showed mortality was higher in patients with obesity class III (BMI ≥ 40 kg/m 2 ). 19 In this study, we examined the association between the BMI classes (patients with underweight [BMI < 18.5 kg/m 2 ], patients with normal weight [BMI 18.5-24.9 kg/m 2 ], patients with overweight [BMI 25-29.9 kg/m 2 ], and patients with obesity [BMI ≥ 30 kg/m 2 ]) and outcomes among patients hospitalized with COVID-19 in our innercity patient population.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study showed the patients with underweight are at risk of mechanical ventilation and death from COVID‐19 16 whereas another study did not show any association of patients with underweight and severity of illness 17 . A more recent study showed that patients with underweight, overweight, and grade 3 obesity were at higher risk of COVID‐19 related mortality compared to patients with grade I or grade II obesity 18 . On the other hand a French study of 1461 critically ill patients with COVID‐19 showed mortality was higher in patients with obesity class III (BMI ≥ 40 kg/m 2 ) 19 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SARS-CoV-2 infection was mainly characterized by acute respiratory symptoms and related systemic complications. The presence of cardio-metabolic (diabetes, hypertension, and obesity) and respiratory (asthma and chronic obstructive pulmonary disease) comorbidities, immunosuppression, and chronic kidney disease (CKD) were all aggravating factors in the evolution and possible triggers for increased mortality in Mexico [ 1 , 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Impaired body composition through weight Fisioterapia Brasil 2023;2491): [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] loss impacts the course of the disease and affects muscles and adipose tissues, making patients even more fragile and worsening these symptoms [2,3]. Among hospitalized patients, underweight patients have higher mortality rates [4]. Within 60 days after hospital discharge 9.1% of patients died, especially older adults [5].…”
Section: Introductionmentioning
confidence: 99%